Negative Effect of Job Insecurity in the Relation between Ethical Leadership and Emotional Exhaustion in Auditor - Yustina, Andi Ina; Satrio, Rudy Aunallah Bumi; Shaleh, Khairul (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
This research examines the moderating role of job insecurity, whether ethical leadership affects emotional exhaustion. A web-based survey is used in deploying and delivering questionnaires to 184 auditors from Indonesia. Result shows that ethical leadership affect significantly towards the emotional exhaustion. The result also demonstrates that job insecurity moderates the effect of ethical leadership on emotional exhaustion. This study suggests that by having leaders with good ethical leadership can reduce the effect of emotional exhaustion in auditors that affected by job insecurity. It is recommended for organization to prevent the effect of emotional exhaustion by training its leaders with ethical leadership development and recruiting ethical leaders.